Mindfulness-based approaches to problematic technology use: A scoping review - Justin Thomas; Fahad Al-Beyahi; Michelle Colder Carras; Dahlia Aljuboori; Saud Alomairah; Johannes Thrul (Computers in Human Behavior Reports)
The inclusion of gaming disorder within the 11th edition of the International Classification of Disease underscored a requirement for treatments targeting problematic technology use. Mindfulness-based interventions (MBIs) have shown early promise. However, questions remain concerning treatment modalities and which populations and conditions are targeted. Additionally, intervention content, effectiveness and the proposed mechanisms of action require summative exploration. This scoping review maps out the emerging literature on MBIs for problematic technology use, addressing the questions above and identifying additional knowledge gaps. Adopting a five-stage methodological framework, ten reports (8 studies) met the eligibility criteria. Positive outcomes were generally reported for MBIs targeting problematic technology use, with improved emotional self-regulation commonly cited as a mechanism of action. Group-based adaptations of existing MBI programs were the norm. There is a clear need for adequately powered randomised active-controlled trials (RCT) of MBIs outside educational settings among culturally and generationally diverse populations. Study reporting was deficient in many areas, impairing the ability to draw firm conclusions. Future research should utilise RCT designs, ensuring the reporting of the intervention content, instructor/therapist credentials, and how treatment fidelity was assured.